Crisis due to war: anxiety, depression and stress in the population of 13 Latin American countries - Mejia, Christian R.; Alvarez-Risco, Aldo; Chamorro-Espinoza, Scherlli; Castillón-Lozano, Jorge Andrés; Paucar, Medally C.; Padilla-F, Valeria J.; Armada, José; Vilela-Estrada, Martin A.; Serna-Alarcón, Victor; Del-Aguila-Arcentales, Shyla; Yáñez, Jaime A. (Frontiers in Psychiatry, 2023)
Sustainability may be at risk in a population that has altered health, according to Sustainable Development Goal 3 (SDG 3): Health and well-being. The ongoing conflict between Russia and Ukraine could jeopardize SDG 3, specifically the mental health of the population. The present study sought to determine the association between severe anxiety, depression and stress in population of 13 Latin American countries according to fear about the war conflict. It was a cross-sectional, analytical and multicenter study. Anxiety, depression and stress were measured with the DASS-21 test (Cronbach's Alpha: 0.97) and fear due to an armed crisis with a questionnaire already validated in Latin America (Cronbach's Alpha: 0.92), which was also adjusted for sex, age, education level and country of residence. Descriptive and analytical statistics were obtained. Of the 2626 respondents, the main fear was that weapons of mass destruction would be used. In the multivariate models, strong associations were found between fear of a possible world-scale armed conflict and having severe or very severe levels of anxiety (aPR: 1.97; 95% CI: 1.64-2.36; p-value < 0.001), depression (aPR: 1.91; 95% CI: 1.54-2.36; p-value < 0.001) or stress (aPR: 2.05; 95% CI: 1.63-2.57; p-value < 0.001). Sustainability linked to SDG 3, specifically mental health, is affected by this type of significant events, given the possible global war crisis that could trigger major events, even more so if added to the deterioration already experienced by COVID-19 in the Latin American region, insecurity and constant political uncertainty.